(untitled) (Forum for Linguistic Studies, 2024)
Kerala, renowned for its distinctive terrain and wildlife, is becoming increasingly exposed to the effects of climate change, such as rising sea levels, frequent floods, and landslides. These trends have caused substantial internal displacement, posing social, economic, and health issues for impacted communities. This article investigates the causes and implications of climate-induced displacement in Kerala, focusing on the role of governance, legal frameworks, and sustainable development. Through case studies and legal research, it reveals inadequacies in disaster management and environmental protection, calling for a holistic approach to resilience-building and human rights protection. Addressing this developing catastrophe will need community involvement, legislative reforms, and international cooperation to limit the effects of climate change and secure sustainable futures for vulnerable people.